The World’s Women 2000 - United Nations Department of Economic; Social Affairs (United Nations, 2000)
The World’s Women 2000: Trends and Statistics is a unique compilation of the latest data documenting progress for women worldwide in six areas: health, human rights and political decision-making, and families. The Report attempts to answer the urgent but complex question of the progress the world’s women are making in their lives. The Report stresses that new data is needed on issues unique to women - such as violence against women and maternal health. The World’s Women 2000 is the third in a series of reports that has broken new ground and the data in the present publication is intended to provide a ’snapshot’ of some of the more salient statistical findings since 1995, while also drawing recent changes and long-term trends. This revealing book remains the most complete description to-date of women’s conditions and contributions worldwide.